Growth Cycles -Transformation and regional development - Karl-Johan Lundquist; Lars-Olof Olander (European Regional Science Association (ERSA), 2010)
Departing from the renewed interest within economic history and neo-Schumpeterian perspectives on growth and economic transformation, we will suggest a theoretical framework for analyzing long term regional economic growth and transformation. Emphasis will be given to different driving forces and their various roles over time, lead-lag relations between industries and how divergence and convergence between regions shift cyclically as consequences of technological change, market integration and economic growth. We claim that systemic approaches in general have been neglected in regional science in favor of "neo-regionalism" in the sense that the study of regional growth has been focusing for years on regional innovation systems and cluster theories without any regard to systemic relations at all. Using detailed time series data and applying a systemic approach we will follow Swedish regions from the structural crises in the mid 1970s to the starting point of the present financial crises. Our results suggest that there are time lags as well as systemic spatial asymmetries between industries and regions leading to changing patterns of divergence and convergence in the regional system. Furthermore, there are indications that the regional disparities between centre and periphery have increased compared to the situation in the mid 1970s.
Keywords: 330